2002
DOI: 10.3168/jds.s0022-0302(02)74116-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Fish Meal and Extruded Soybeans Enhances the Conjugated Linoleic Acid (CLA) Content of Milk

Abstract: Twelve multiparous Holstein cows averaging 65 (33 to 122) DIM were used in a 4 x 4 Latin square for 4-wk periods to determine whether feeding fish oil as fish meal would stimulate increased amounts of milk conjugated linoleic acid (cis-9, trans-11 C18:2; CLA) and transvaccenic acid (trans-11 C18:1; TVA) when the cows were fed extruded soybeans to supply additional linoleic acid. Treatment diets were 1) control; 2) 0.5% fish oil from fish meal; 3) 2.5% soybean oil from extruded soybeans; and 4) 0.5% fish oil fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
74
2
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 21 publications
14
74
2
4
Order By: Relevance
“…In the research conducted so far, cis fatty acids have been the main object of study in addition to the rumen synthesis of CLA C18:2 (Abuhazaleh et al, 2002;Brzóska, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the research conducted so far, cis fatty acids have been the main object of study in addition to the rumen synthesis of CLA C18:2 (Abuhazaleh et al, 2002;Brzóska, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Milk fatty acid composition has been shown to be affected by dietary oil supplementation (Huang et al 2008). A number of studies have also demonstrated that dietary fish oil supplements alter the pathways of ruminal biohydrogenation, and lead to the accumulation of trans-11 C18:1 in milk (Abu-Ghazaleh et al 2002;Whitlock et al 2002). Donovan et al (2000) reported that dietary inclusion of fish oil (20 g/kg of diet DM) increased cis-9, trans-11 conjugated linoleic acid concentrations in milk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated an increase in the vaccenic acid (VA) and c9t11 CLA content of bovine milk fat when fish oil (FO) and linoleic acid oil sources were added to dairy cattle rations containing 50% forage (AbuGhazaleh et al, 2000;Whitlock et al, 2002). Studies examining the effect of forage or concentrate feeding on the distribution of trans C18:1 and CLA isomers in the rumen (Loor et al, 2004a) or ruminant fat (Sackmann et al, 2003;Aharoni et al, 2004;Loor et al, 2005) have used only vegetable oils or FO.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the profile of trans C18:1 intermediates formed in the rumen have direct consequences on the supply of VA available for endogenous conversion in the mammary gland into c9t11 CLA . Previously, AbuGhazaleh et al (2000AbuGhazaleh et al ( , 2003 and Whitlock et al (2002) demonstrated that the greatest concentrations of VA and c9t11 CLA in milk fat and rumen contents can be obtained by adding FO along with linoleic acid fat source to ruminant animals' diet. The aim of this study was to investigate how changing dietary forage levels in diets containing FO and sunflower oil (SFO) affect trans C18:1 and CLA isomers distribution in the rumen.…”
Section: Introductionmentioning
confidence: 99%